2021
DOI: 10.53713/nhs.v1i2.41
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Health Promotion of Animation Videos on Behavior of Prevention of Dengue Heavenly Fever In the Work Area of Health Center, Sunday Market District South Jakarta City Year 2021

Abstract: Dengue hemorrhagic fever is one of the leading causes of morbidity and mortality in the community. One of the efforts made in preventing DHF is through various health promotions by providing information and communication. Such as counseling and campaigns, electronic media, print media, and so on to increase knowledge, attitudes, and practices in the community to have awareness in changing and improving their health status. This study aims to determine the effect of health promotion through animated videos on k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Explanations can be played repeatedly with visual demonstrations and made as attractive as possible, like animated cartoons that interest respondents in learning. Listening accelerates someone's understanding, which can immediately change their behavior (Aisyiah, Wowor, & Ahufruan, 2021).…”
Section: Parents' Attitudes In Performing Hyperthermia First Aid In P...mentioning
confidence: 99%
“…Explanations can be played repeatedly with visual demonstrations and made as attractive as possible, like animated cartoons that interest respondents in learning. Listening accelerates someone's understanding, which can immediately change their behavior (Aisyiah, Wowor, & Ahufruan, 2021).…”
Section: Parents' Attitudes In Performing Hyperthermia First Aid In P...mentioning
confidence: 99%
“…Moreover, respondents' skills after being given health education in splints on average in the good category of 20 respondents (60.6%) (Listiana & Oktarina, 2019). Another study showed that the average value of attitudes towards preventing dengue hemorrhagic fever before giving health promotion through the video method was 49.61 and the average value of attitudes after being given an intervention through health promotion videos was 59.14 (Aisyiah et al, 2021). They were filling out a questionnaire regarding the knowledge of splint dressing in the intervention and control groups after health education had generally increased.…”
Section: The Level Of the Knowledge Level Of Splint Dressing After Sp...mentioning
confidence: 99%
“…Health education is an effort made by a person, group, or community to achieve relationships and abilities toward a good direction in everyday life (Setioputro et al, 2022). Health promotion is an effort or activity to create community behavior conducive to health (Aisyiah et al, 2021). Health workers are responsible as educators for conveying information to motivate patients about the importance of learning .…”
Section: Introductionmentioning
confidence: 99%